Structural and Mechanical Properties of Hot Rolled CuAlBe Non-Spark Alloy Explosion - G.R. Chelariu; N. Cimpoeșu; P. Paraschiv; B.A. Prisecariu; I. Rusu; I. Știrbu; G.I. Sandu; M. Benchea; C. Bejinariu (Archives of Metallurgy and Materials, 2024)
Explosion protection is of particular importance for safety as explosions also endanger the health of workers due to the uncontrolled effects of flames and pressure, the presence of harmful reaction products and the consumption of oxygen in the ambient air breathed by workers. CuAlBe alloy is proposed as a solution for mechanical actuators such as gears that work in environments with possible explosive atmosphere. Made of CuBe master alloy and pure aluminum in a induction furnace the material present large grains in melted state. After the hot rolling (heated 600s at 900°C) of the ingots small variation of chemical composition was observed based on the oxidation of the material, appearance of small cracks on the edges and a preferential orientation of the grains along the lamination direction. Scanning electron microscopy (SEM) was used to characterize the microstructural states of CuAlBe as laminated and heat treated states.